1985
DOI: 10.1007/bf00492453
|View full text |Cite
|
Sign up to set email alerts
|

Studies on vinblastine-induced autophagocytosis in mouse liver

Abstract: The origin and the structure of the limiting membranes of autophagic vacuoles (AV) in mouse hepatocytes was studied using cytochemical techniques. Autophagocytosis was induced by an intraperitoneal injection of vinblastine (50 mg/kg). Imidazole-buffered osmium tetroxide impregnation was used as a marker for unsaturated fatty acids, and uranyl-lead-copper impregnation for the determination of possible connections of AV membranes with the other cellular membranes. AV membranes stained strongly with both techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 21 publications
4
35
0
1
Order By: Relevance
“…In hepatocytes, the majority of reports favors the membranes of ER and Golgi apparatus as the original membrane of autophagic vacuoles from the evidence such as occasional direct continuity of ER membranes with the outer limiting membrane of autophagic vacuoles (14) and the osmium-staining common property of the autophagic vacuole membrane with ER and Golgi apparatus membranes (9). In contradicton, it has been recently reported that the limiting membranes of autophagic vacuoles possess characteristics distinct from the ER and Golgi membranes with respect to the density of intramembranous particles (8,19) and the concentration of cholesterol and unsaturated fatty acids (18). Our finding that the membranes of autophagic vacuoles carry a net negative charge exceeding that of other intracellular membranes is compatible with such a change in membrane composition during the course of formation of autophagic vacuoles.…”
supporting
confidence: 79%
“…In hepatocytes, the majority of reports favors the membranes of ER and Golgi apparatus as the original membrane of autophagic vacuoles from the evidence such as occasional direct continuity of ER membranes with the outer limiting membrane of autophagic vacuoles (14) and the osmium-staining common property of the autophagic vacuole membrane with ER and Golgi apparatus membranes (9). In contradicton, it has been recently reported that the limiting membranes of autophagic vacuoles possess characteristics distinct from the ER and Golgi membranes with respect to the density of intramembranous particles (8,19) and the concentration of cholesterol and unsaturated fatty acids (18). Our finding that the membranes of autophagic vacuoles carry a net negative charge exceeding that of other intracellular membranes is compatible with such a change in membrane composition during the course of formation of autophagic vacuoles.…”
supporting
confidence: 79%
“…48 The freeze-fracture technique was also used by Eeva-Liisa Eskelinen (then using the surname Punnonen), in combination with filipin staining to show that autophagosomal delimiting membranes were exceptionally poor in cholesterol. 47 Furthermore, since osmic acid impregnation selectively stains unsaturated fatty acids, the strong osmiophilicity of autophagosome delimiting membranes 34,35,[50][51][52] and their sequestering precursors 38,53 indicated that they are rich in unsaturated fatty acids. As explained later, these membranes also have unique surface charge properties.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Based on morphological, cytochemical and immunoelectron microscopy data, autophagosomes are proposed to originate from the membranes of the endoplasmic reticulum. 11 However, the structural and biochemical characteristics of these membranes are different from the endoplasmic reticulum, [35][36][37][38] and thus the phagophores or isolation membranes should probably be regarded as distinct organelles.…”
Section: Autophagy Genesmentioning
confidence: 99%